2010
DOI: 10.1016/j.geobios.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intraspecific variability in the chemical composition of the mineral phase of cements from several tube-building polychaetes

Abstract: Inter-and intraspecific variability in the chemical composition of the mineral phase of cements from several tube-building polychaetes § Variabilité inter-et intraspécifique de la composition chimique de la phase minérale des ciments utilisés dans la construction du tube de plusieurs polychètes bioconstructeurs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Here, however, seasonal differences were mainly driven by an invertebrate species, the polychaete Sabellaria alveolata, which was more abundant in winter than in summer. This species is responsible for the construction of the largest biogenic reefs in Europe, providing a highly dynamic habitat for diversified associated organisms (Dubois et al 2002, Fournier et al 2010. Sabellaria alveolata reefs were indicated as extremely sensitive to the mechanical impact of natural (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Here, however, seasonal differences were mainly driven by an invertebrate species, the polychaete Sabellaria alveolata, which was more abundant in winter than in summer. This species is responsible for the construction of the largest biogenic reefs in Europe, providing a highly dynamic habitat for diversified associated organisms (Dubois et al 2002, Fournier et al 2010. Sabellaria alveolata reefs were indicated as extremely sensitive to the mechanical impact of natural (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…1). It is also only the second location where the species is recorded in Brazil's northern coastline, after Kirtley (1994), Fausto-Filho and Furtado (1970) and Fournier et al (2010) had recorded it for Fortaleza, Ceará (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…1). Fournier et al (2010) examined the inter-and intraspecific variability on chemical composition of biocement among sand-reef-building polychaetes, including Brazil- ian populations previously recorded as P. caudata or P. lapidosa Kinberg 1867 from the following states: Santa Catarina, Paraná, São Paulo, Rio de Janeiro, Paraíba, Rio Grande do Norte and Ceará. These authors concluded that there is some degree of variation on the cement's biochemistry among populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two species have attracted most of the attention in terms of tube building: Sabellaria alveolata and Phrag matopoma californica. The former was investigated mainly in terms of tube structure, building organ morphology, and cement elemental analysis (Vovelle, 1965;Gruet et al, 1987;Fournier et al, 2010); the latter was described in terms of building organ morphology and micro-and nano structure as well as composition of the cement (Stewart et al, 2004;Zhao et al, 2005;Stevens et al, 2007;Wang et al, 2010;Wang and Stewart, 2012). Among sabellariids, P. californica is the only species in which cement proteins have been characterized.…”
Section: Discussionmentioning
confidence: 99%